2022
DOI: 10.3389/fonc.2022.780716
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Landscape in Neuroendocrine Tumors With High-Grade Features: Current Knowledge and Future Perspective

Abstract: Neuroendocrine tumors (NETs) are classified based on morphology and are graded based on their proliferation rate as either well-differentiated low-grade (G1) to intermediate (G2–G3) or poorly differentiated high-grade neuroendocrine carcinomas (NEC G3). Recently, in gastroenteropancreatic (GEP) NETs, a new subgroup of well-differentiated high-grade tumors (NET G3) has been divided from NEC by WHO due to its different clinical–pathologic features. Although several mutational analyses have been performed, a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 136 publications
1
10
0
Order By: Relevance
“…This was similar to the findings of Tsuruoka et al's study that PD‐L1 expression was not observed in NETs 22 . Mismatch repair protein deficiency was rare in pancreatic and intestinal NETs 23 . In another study, microsatellite instability (MSI) was confirmed in only 3 (1.3%) of 239 NENs, and all MSI was present in cecal NECs, with MSI being uncommon in other NENs 24 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This was similar to the findings of Tsuruoka et al's study that PD‐L1 expression was not observed in NETs 22 . Mismatch repair protein deficiency was rare in pancreatic and intestinal NETs 23 . In another study, microsatellite instability (MSI) was confirmed in only 3 (1.3%) of 239 NENs, and all MSI was present in cecal NECs, with MSI being uncommon in other NENs 24 .…”
Section: Discussionsupporting
confidence: 88%
“… 22 Mismatch repair protein deficiency was rare in pancreatic and intestinal NETs. 23 In another study, microsatellite instability (MSI) was confirmed in only 3 (1.3%) of 239 NENs, and all MSI was present in cecal NECs, with MSI being uncommon in other NENs. 24 Most of the patients in our study had rectal NETs (33 cases), and only three cases were rectal NECs.…”
Section: Discussionmentioning
confidence: 97%
“…Variations in genomic profile aid in differentiating neuroendocrine carcinomas (NECs) and NETs and determining treatment response [ 20 ]. Common mutations reported in the literature involved in NECs include TP53, KRAS, and RB1, and these are associated with poor differentiation of the carcinoma [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in genomic profile aid in differentiating neuroendocrine carcinomas (NECs) and NETs and determining treatment response [ 20 ]. Common mutations reported in the literature involved in NECs include TP53, KRAS, and RB1, and these are associated with poor differentiation of the carcinoma [ 20 ]. TP53 and RB1 are mutated in about 80% of poorly differentiated neuroendocrine neoplasms (NENs), and data from mouse models indicate that the loss of these two genes is vital to the formation of poorly differentiated NENs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation